SL15: A seminal plasma-derived lectin from the sperm of llama (Lama glama) - Zampini, Renato (2017)
The oviductal sperm reservoir of South American camelids is formed when sperm bind to N-acetylgalactosamine (GalNAc) on the surface of oviductal epithelium. The aim of this study was to characterize the GalNAc-binding proteins on llama sperm, and to establish their origin. Sperm-adsorbed proteins were extracted with 0.5 M KCl in Hepes-balanced salts. Sperm-adsorbed and seminal plasma proteins were then subjected to ligand blotting for their GalNAc affinity, and the labeled bands were identified by mass spectrometry. Three proteins were identified in seminal plasma versus only one in the sperm-adsorbed population; SL15, a seminal lectin, was common to both. SL15 is a homologue of Zymogen granule protein 16, homolog B-like, which belongs to the Jacalin-related lectin family. This lectin is likely presented to sperm via seminal plasma since epididymal sperm are not capable of binding GalNAc, whereas ejaculated sperm does, and its transcript was enriched predominantly in the prostate and bulbourethral glands. This is the first report of a seminal lectin in South American camelids that originates in the male reproductive tract, and is probably involved in sperm reservoir formation.